Análisis de la metodología DMAIC como un modelo de mejora continua para el sector productivo de las PYMES de alimentos en la provincia de pichincha entre 2008-2012 - Oña Paucar, Verónica Patricia (2014)
The paper presents the study progress concerning the diagnosis of food SMEs in the province of Pichincha to make a proposal to implement DMAIC Improvement tool, in order to enable them to adopt this methodology as a strategy for the development of essential their competitive position. The study focuses on identifying critical factors that directly affect the competitive performance of SMEs in food; likewise the knowledge we have regarding the DMAIC methodology, and if some other method to improve and increase their competitive performance is used. The proposal aims to contribute to the generation of alternatives for achieving SMEs more effective, innovative and efficient.